Chapter Crystallization of Membrane Proteins: Merohedral Twinning of Crystals - Borshchevskiy, V.; Gordeliy, V. (InTechOpen, 2012)
Environmental management
English
Keywords: Food security & supply; Earth sciences, geography, environment, planning